Efficiency of a radiofrequency sealer (Aquamantys) for parenchymal transection during laparoscopic hepatectomy. Issue 4 (29th January 2020) - Iida, Hiroya; Maehira, Hiromitsu; Mori, Haruki; Tani, Masaji
Abstract: Introduction: The methods of liver parenchymal transection vary across institutions. In this study, we used a radiofrequency (RF) sealer (Aquamantys) as a hemostatic device during laparoscopic liver transection; we also evaluated the usefulness of RF sealers. Methods: From April 2016 to May 2019, 113 consecutive laparoscopic hepatectomy patients, excluding patients with combined resection of other organs, were examined. Patient characteristics, operative factors, and postoperative complications were compared between the Cavitron ultrasonic surgical aspirator (CUSA) + soft coagulation system (VIO) group; (n = 32) and the CUSA + Aquamantys group; (n = 81). The former underwent liver transection by CUSA and VIO from April 2016 to March 2017, while the latter underwent liver transection using CUSA and Aquamantys from April 2017 to May 2019. Results: The median difficulty score was significantly higher in the CUSA + VIO group (5.5 points vs 5.0 points; P = .04). Blood loss per unit area and the liver parenchymal transection speed were not significantly different between the groups. After propensity score matching, blood loss per unit area was similar between the groups, but the parenchymal transection speed of the CUSA + Aquamantys group was significantly higher (0.92 cm 2 /min vs 0.64 cm 2 /min; P = .017). Postoperative complications were similar between the groups. Conclusion: In laparoscopic hepatectomy, hemostasis of the transection plane with an RF sealer did not reduce blood loss during parenchymal transection. However, the liver parenchymal transection speed was increased.